Bipolar anodal septal pacing with direct LBB capture preserves physiological ventricular activation better than unipolar left bundle branch pacing - Curila, Karol; Jurak, Pavel; Prinzen, Frits; Jastrzebski, Marek; Waldauf, Petr; Halamek, Josef; Tothova, Marketa; Znojilova, Lucie; Smisek, Radovan; Kach, Jakub; Poviser, Lukas; Linkova, Hana; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Left bundle branch pacing (LBBP) produces delayed, unphysiological activation of the right ventricle. Using ultra-high-frequency electrocardiography (UHF-ECG), we explored how bipolar anodal septal pacing with direct LBB capture (aLBBP) affects the resultant ventricular depolarization pattern. Methods: In patients with bradycardia, His bundle pacing (HBP), unipolar nonselective LBBP (nsLBBP), aLBBP, and right ventricular septal pacing (RVSP) were performed. Timing of local ventricular activation, in leads V1-V8, was displayed using UHF-ECG, and electrical dyssynchrony (e-DYS) was calculated as the difference between the first and last activation. Durations of local depolarizations were determined as the width of the UHF-QRS complex at 50% of its amplitude. Results: aLBBP was feasible in 63 of 75 consecutive patients with successful nsLBBP. aLBBP significantly improved interventricular dyssynchrony (−9 ms (−12;−6) vs. −24 ms (−27;−21), ), p ˂ 0.001) and shortened local depolarization durations in V1–V4 (mean differences −7 ms to −5 ms (−11;−1), p ˂ 0.05) compared to nsLBBP. Both aLBBP and HBP caused similar absolute levels of interventricular dyssynchrony (e-DYS −9 ms (−12; −6) vs. 10 ms (7;14); however, local depolarization durations in V1–V2 during aLBBP were longer than HBP (differences 5–9 ms (1;14), p ˂ 0.05, with local depolarization duration in V1 during aLBBP being the same as during RVSP (difference 2 ms (−2;6), p = 0.52). Conclusion: Although aLBBP significantly improved interventricular synchrony and depolarization duration of the septum and RV compared to unipolar nsLBBP, the resultant ventricular depolarization was still less physiological than during HBP.